Barriers to Medication Adherence Among Patients with Non-Communicable Disease in North Wollo Zone Public Hospitals: Socio-Ecologic Perspective, 2023 - Fenta ET; Ayal BG; Kidie AA; Anagaw TF; Mekonnen TS; Ketema Bogale E; Berihun S; Tsega TD; Mengistie Munie C; Talie Fenta T; Kassie Worku N; Shiferaw Gelaw S; et al. (Patient Preference and Adherence, 2024)
Eneyew Talie Fenta,1 Birtukan Gizachew Ayal,2 Atitegeb Abera Kidie,2 Tadele Fentabil Anagaw,3 Tesfaye Shumet Mekonnen,2 Eyob Ketema Bogale,3 Sileshi Berihun,1 Tilahun Degu Tsega,1 Chernet Mengistie Munie,4 Tizazu Talie Fenta,5 Nigus Kassie Worku,6 Sintayehu Shiferaw Gelaw,7 Misganaw Guadie Tiruneh8 1Department of Public Health, College of Medicine and Health Sciences, Injibara University, Injibara, Ethiopia; 2Department of Public Health, College of Medicine and Health Sciences, Woldia University, Woldia, Ethiopia; 3Department of Health Promotion and Behavioral Science, School of Public Health, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 4Resource Mobilization Directorate, Amhara Regional health Bureau, Bahir Dar, Ethiopia; 5Department of Medical Laboratory Science, Gamby Medical and Business College, Bahir Dar, Ethiopia; 6Department of Public Health, College of Medicine and Health Science, Dire Dawa University, Dire Dawa, Ethiopia; 7Department of Public Health, College of Medicine and Health Science, Debre Markos University, Debre Markos, Ethiopia; 8Department of Health System and Policy, Institute of Public Health, College of Medicine and Health Science University of Gondar, Gondar, EthiopiaCorrespondence: Eneyew Talie Fenta, Email eneyew89@gmail.comBackground: The practice of taking medication as directed by a healthcare provider is known as medication adherence. Therefore, the application of a socio-ecological model to this study identifies multilevel factors on barriers of medication adherence on chronic non-communicable disease and provides information to develop scientific health communication interventional strategies to improve medication adherence.Objective: This study aimed to explore barriers of medication adherence on non-communicable disease prevention and care among patients in North Wollo Zone public hospitals, northeast Ethiopia.Methods: A phenomenological study design was carried out between February 5 and February 30, 2023. The study participants were chosen using a heterogeneous purposive sampling technique. In-depth interviews and targeted focus groups were used to gather data. The focus group discussions and in-depth interviews were captured on audio, accurately transcribed, and translated into English. Atlas TI-7 was utilized to do the thematic analysis.Results: Four main themes, intrapersonal, interpersonal, community level, and health care related, as well as seven subthemes, financial problems, lack of family support, poor communication with healthcare providers, effects of social ceremonies, remote healthcare facility, and drug scarcity, were identified by this study. In this study participants reported that lack of knowledge about the disease and drugs were the main barrier for medication adherence. The study revealed that financial problems for medication and transportation cost were the main factor for medication adherence for non-communicable disease patients.Conclusion: This study explored that lack of knowledge, financial problem, lack of family support, poor communication with healthcare providers, social ceremony effects, remote healthcare facility, and scarcity of drugs were barriers of medication adherence among non-communicable disease patients. In order to reduce morbidity and mortality from non-communicable diseases, it is advised that all relevant bodies look for ways to reduce medication adherence barriers for patients at every level of influence.Keywords: medication adherence, socio-ecological model, non-communicable disease